Heat transfer test method development: Consideration for design and safety of household oven mitts - Adriana Petrova; Semra Peksoz; Aditya Jayadas (Communications in Development and Assembling of Textile Products)
The purpose of this study was to develop a test method – an apparatus and a protocol for evaluating the rate of heat transfer across a sample of layered materials commonly used in oven mitts. Using the apparatus, effects of contact temperature and pressure as well as design features such as quilting stitching pattern of the sample on heat transfer were examined. The apparatus featured a round wooden base with three silicone-covered wooden “fingers” equipped with thermocouples where the test samples were mounted. The device was lowered with the samples down onto a hot plate kept at stable high “pan” contact temperature. Upon contact, changes of the “skin” contact temperatures (at the “fingers”) were recorded at 10 Hz for 300 s. Tests were carried out at six levels of pressure on the sample (exerted by variable weights), 3 levels of “pan” contact temperature, and 3 different quilting stitch patterns of the material. Time to reach critical skin threshold temperature was affected by stitch pattern; it decreased exponentially with increasing pressure and increasing hot plate contact temperature. The shape of the temperature-time curve indicated how the material configuration of the sample affects the transfer of heat.